Analysis of Air Flow Characteristics on a Savonius Wind Turbine Next to a Building through CFD Simulation - Aulina, Audha Fitrah; Hasbiyati, Haning (invotek, 2025)
Urban environments pose significant challenges for wind energy utilization due to highly complex, non-uniform, and turbulence-dominated airflow around buildings. Although the Savonius vertical-axis turbine is capable of operating under such conditions, its performance remains highly sensitive to installation placement and configuration. This study conducts a two-dimensional CFD investigation to evaluate the aerodynamic behavior of two tandem-arranged Savonius turbines mounted adjacent to a wall. Two blade-orientation configurations are assessed: Configuration 1, where the returning blades face each other, and Configuration 2, where the advancing blades are adjacent. Transient simulations employing a validated CFD framework with the Realizable k-ε turbulence model are performed at a 7 m/s inflow velocity across a range of tip speed ratios. The results reveal pronounced wall–flow interactions characterized by flow deflection and blockage effects. Configuration 2 demonstrates superior aerodynamic performance, achieving a higher maximum power coefficient over a broader TSR range. This improvement is attributed to a favorable “nozzle effect” generated between the advancing blade of the front turbine and the wall, which accelerates the incoming flow toward the rear turbine and enhances its inflow conditions. In contrast, Configuration 1 exhibits stronger wake interference and more severe blockage, particularly at higher TSR values. Overall, the findings indicate that an adjacent advancing-blade arrangement optimizes aerodynamic interaction and energy extraction for wall-mounted tandem Savonius turbines, offering valuable insights for the design of small-scale urban wind energy systems.